2011
DOI: 10.1002/ange.201101450
|View full text |Cite
|
Sign up to set email alerts
|

One β Hairpin Follows the Other: Exploring Refolding Pathways and Kinetics of the Transmembrane β‐Barrel Protein OmpG

Abstract: Eine nach der anderen: Mithilfe der Einzelmolekül‐Rasterkraftspektroskopie wurde ein Außenmembranprotein mit β‐Fass‐Struktur in die native Lipidmembran gefaltet. Überraschenderweise falten die β‐Stränge von OmpG aus E. coli nicht einzeln, sondern als β‐Haarnadeln eine nach der anderen, bis das gesamte Protein gefaltet ist (siehe Bild). Dieser Mechanismus erweitert das Verständnis über derzeitige Faltungsmodelle von Proteinen mit β‐Fass‐Struktur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…As expected from previous studies, [7a, 8b, 12] loop 6 performs the major gating function. When it was pinned to the membrane, a constitutively open pore was found with properties quite similar to those of quietOmpG (Figure S3).…”
supporting
confidence: 85%
“…As expected from previous studies, [7a, 8b, 12] loop 6 performs the major gating function. When it was pinned to the membrane, a constitutively open pore was found with properties quite similar to those of quietOmpG (Figure S3).…”
supporting
confidence: 85%
“…In the case of transmembrane a-helical proteins, it was shown that the mechanically stressed polypeptide not only induces the stepwise unfolding of the membrane protein but also folds back stepwise into the membrane bilayer (Kedrov et al, 2006;Kedrov et al, 2004;Kessler et al, 2006). Similarly, mechanically loaded OmpG unfolds stepwise and refolds stepwise into the membrane (Damaghi et al, 2011). Here we show that when mechanically stressing the PGBD of KpOmpA, transmembrane b-strands form stable unfolding intermediates and, as soon as the tensile load disappears, fold back into the lipid membrane.…”
Section: Possible Extension Of the Two-state Folding And Insertion Momentioning
confidence: 99%
“…Such mechanical stress may be expected when bacteria adhering to surfaces are exposed to hydrodynamic flow or undergo severe mechanical deformations (Otto et al, 2001). It has also been shown that b barrel proteins once unfolded by mechanical force can insert and fold back into the lipid membrane (Bosshart et al, 2012a;Damaghi et al, 2011). Thereby the unfolded polypeptide can insert one b hairpin after the other until folding of the b barrel has been completed.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case, periplasmic chaperones can prevent misfolding and support the stepwise insertion and folding of b hairpins toward the native membrane protein structure (Thoma et al, 2015). Thus, studying the mechanical unfolding of b barrel proteins can provide complementary mechanistic insight into their folding behavior (Bosshart et al, 2012a;Damaghi et al, 2011;Horne and Radford, 2016;Thoma et al, 2015). In previous studies we used AFM-based SMFS to investigate the mechanical unfolding of bacterial outer membrane proteins having different sizes: (1) the small outer membrane protein OmpA from Klebsiella pneumoniae comprising eight b strands (Bosshart et al, 2012a), (2) the intermediate-sized outer membrane protein OmpG from Escherichia coli comprising 14 b strands (Sapra et al, 2009), and (3) the large outer membrane protein FhuA from E. coli comprising 22 b strands (Thoma et al, 2012) Here we attempt to gain a deeper understanding of the mechanical unfolding pathways of outer membrane proteins observed so far and apply SMFS to unfold another b barrel membrane protein maltoporin (LamB) from E. coli.…”
Section: Introductionmentioning
confidence: 99%